2023
DOI: 10.15252/embj.2023114415
|View full text |Cite
|
Sign up to set email alerts
|

Cell fragmentation in mouse preimplantation embryos induced by ectopic activation of the polar body extrusion pathway

Abstract: Cell fragmentation is commonly observed in human preimplantation embryos and is associated with poor prognosis during assisted reproductive technology (ART) procedures. However, the mechanisms leading to cell fragmentation remain largely unknown. Here, light sheet microscopy imaging of mouse embryos reveals that inefficient chromosome separation due to spindle defects, caused by dysfunctional molecular motors Myo1c or dynein, leads to fragmentation during mitosis. Extended exposure of the cell cortex to chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Since this signaling cascade occurs when maternal/paternal chromatin is in close vicinity to the cortex, it is reasonable to speculate that it may be conserved in oocytes from other species. Intriguingly, a recent study by Pelzer and colleagues reported that the pathway for chromosome-induced cortical contractility remains active in preimplantation embryos and may lead to blastomere fragmentation if mitotic chromosomes come near the cortex for an extended duration ( Pelzer et al, 2023 ). In dividing somatic cells however, the scenario is quite the opposite, as Ran·GTP was shown to promote myosin II depletion from the chromosome-proximal polar cortex, thereby allowing for membrane expansion ( Kiyomitsu and Cheeseman, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since this signaling cascade occurs when maternal/paternal chromatin is in close vicinity to the cortex, it is reasonable to speculate that it may be conserved in oocytes from other species. Intriguingly, a recent study by Pelzer and colleagues reported that the pathway for chromosome-induced cortical contractility remains active in preimplantation embryos and may lead to blastomere fragmentation if mitotic chromosomes come near the cortex for an extended duration ( Pelzer et al, 2023 ). In dividing somatic cells however, the scenario is quite the opposite, as Ran·GTP was shown to promote myosin II depletion from the chromosome-proximal polar cortex, thereby allowing for membrane expansion ( Kiyomitsu and Cheeseman, 2013 ).…”
Section: Discussionmentioning
confidence: 99%